(untitled) (Journal of Rangpur Medical College, 2025)
Background: Headaches are a common issue among children, affecting their daily functioning and quality of life. Objective: This study aimed to explore the distribution of headaches in children, examining factors such as age, sex, BMI, dietary habits, sleep patterns, and potential triggers. Methods: A cross-sectional study was conducted on 245 children aged 7 to <18 years, including 120 diagnosed with Migraine or Tension-Type Headache (TTH) at pediatric OPD of National Institute of Neurosciences and Hospital, Dhaka, and 125 age-matched healthy siblings. Headache diagnoses followed ICHD-3 criteria. A structured questionnaire was administered to gather data on lifestyle factors such as sleep patterns, dietary habits, leisure activities, BMI, environmental triggers, academic stress, and family dynamics. Data collection was carried out through face-to-face interviews with parents and children, after obtaining informed consent. SPSS software was used for data analysis. Results: Among the headache group, 45% of children with Migraine and 66.7% of those with TTH were in the 10-12 years age group. The study revealed a significant relationship between abnormal sleep patterns (sleep latency >30 minutes, <8 hours sleep duration, TV/mobile usage before sleep, and daytime naps) and the occurrence of headaches (p<0.05). However, no significant associations were found with other lifestyle factors like diet, physical activity, or obesity. Conclusion: The findings suggest a significant relationship between sleep disturbances and headaches in children. Given the impact on quality of life, further research is needed to explore the broader lifestyle influences on headache prevalence among children and adolescents. J Rang Med Col. 2025 Sep;10(2): 103-108